The Consumer Protection on Access to Information on Sugar, Salt, and Fat - Muhammad Mufti Mubarok (Journal of Consumer Sciences, 2023)
Around 70 percent of deaths in Indonesia are non-communicable diseases (NCDs) due to excessive consumption of sugar, salt, and fat. This study aims to determine consumer protection over sugar, salt, and fat information access. This research used a descriptive qualitative approach. Data were collected in March 2022 through Focus Group Discussions with informants from regulators, business associations, and consumer protection activists, as well as field observations in South Tangerang City and Semarang. The sampling method used was purposive sampling. Government regulations, business compliance, and supervision influence consumer rights to access sugar, salt, and fat information. Government regulations are still limited, and there needs to be an explanation of the implementation and standards. Many modern and traditional retailers still need to include information about sugar, salt, and fat, as well as health messages, in their product packaging. The government needs to intensify socialization and educate business actors regarding the obligation to include nutritional value information and health messages. Consumers also need to be educated about the dangers of excessive sugar, salt, and fat consumption and the nutritional literacy of their products.